Kay Boyle et la revue transition (1927-1938) : « A new meaning to my life » - Céline MANSANTI (E-REA)
This paper focuses on the impact of American exile little magazine transition (Paris, 1927-1938) on Kay Boyle’s intellectual growth and career and, conversely, on Boyle’s contribution to transition’s modernism. transition played a key role in Boyle’s life and career: an exceptional publishing venue—she contributed twenty poems and short stories to the magazine—, transition was also invaluable for the support she found with Jolas, the new writings she discovered—especially those of the surrealists—and the encounters that boosted her professional life. Moreover, Jolas’ “Revolution of the Word” project allowed Boyle to join what she called a new literary tradition: in her case, a progressive kind of modernism, characterized by its feminism and its capacity to mix highbrow and popular cultures, aesthetic investigations and political commitment. However, from 1932 on, Boyle had but one text published in transition, mainly because of her involvement in a new politically-committed avant-garde, remote from transition’s concerns.